Considerations in surgical management of a Buschke–Lowenstein tumor in Netherton syndrome: A case report. Issue 6 (16th November 2017) - Ashton, Rosalind; Moledina, Jamil; Sivakumar, Branavan; Mellerio, Jemima E.; Martinez, Anna E.
Abstract: Netherton syndrome is an autosomal recessive ichthyosis caused by mutations in SPINK5, with the classic triad of linearis circumflexa, trichorrhexis invaginata, and atopy. There are few reports of surgical management in individuals with Netherton syndrome and clinicians may be reluctant to operate for fear of wound‐healing complications. This report describes a pediatric case of a Buschke–Lowenstein tumor of the natal cleft in a patient with Netherton syndrome that had failed to respond to medical management. We reviewed the literature for previous cases of surgery in individuals with Netherton syndrome using MEDLINE and PubMed searches. Our patient underwent surgery to remove the lesion without complication. Using conventional dressings and topical negative‐pressure therapy, the wound was managed and healed within a reasonable time frame despite the underlying skin condition. This case indicates that surgery and topical negative‐pressure therapy is a safe and reasonable treatment for individuals with Netherton syndrome.